The Mormon Vanguard Brigade of 1847: Norton Jacob's record - Jacob, Norton, 1804-1879, author; Barney, Ronald O., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2005)
The diary published here begins in 1844, the year of Mormon church founder Joseph Smith's murder. It continues through the crisis events that followed, including the Mormons' flight from Nauvoo and the beginnings of mass migration to Utah. After the apex of 1847, the arc of the narrative moves through accounts of Norton Jacob's return to Nauvoo late that year and of the much larger Mormon emigration in 1848. It reaches denouement in a short record of his first years in Salt Lake Valley.
Norton Jacob's life -- Reminiscence and 1844 -- 1845 -- 1846 -- January-April 1847 -- May 1847 -- June 1847 -- July 1847 -- August 1847 -- September-December 1847 -- 1848 -- 1849-1852 -- Appendix 1: Norton Jacob's genealogy -- Appendix 2: Mormon vanguard brigade of 1847.
Keywords: Jacob, Norton, 1804-1879. Record of Norton Jacob; Mormon pioneers -- Diaries; Jacob, Norton, 1804-1879 -- Diaries